Intussusception in adult due to appendicular invagination causing sub-acute intestinal obstruction - Singh, Akanand; Sah, Rakesh Kumar (Grande Medical Journal, 2024)
We are presenting a case of 48 year old female presented to us with the compliant of mild pain over right lower abdomen for one week. On evaluation, Plain CT scan showed features of ileocolic intussusceptions (Figures 1, 2, and 3). Preoperative evaluation was done and patient was taken for surgery. We performed laparoscopic assisted ileo-caeccal resection and anastomosis which was uneventful. There was appendix invagination into the caecum extending to ascending colon. Patient was discharged from hospital on post-operative day five. Histopathology result showed margin free low grade appendiceal mucinous neoplasm.